Breakup Without Borders: How Continents Speed Up and Slow Down During Rifting - Martina M. Ulvrova; Sascha Brune; Simon Williams (Geophysical Research Letters)
Abstract Relative plate motions during continental rifting result from the interplay of local with far‐field forces. Here we study the dynamics of rifting and breakup using large‐scale numerical simulations of mantle convection with self‐consistent evolution of plate boundaries. We show that continental separation follows a characteristic evolution with four distinctive phases: (1) an initial slow rifting phase with low divergence velocities and maximum tensional stresses, (2) a synrift speed‐up phase featuring an abrupt increase of extension rate with a simultaneous drop of tensional stress, (3) the breakup phase with inception of fast sea‐floor spreading, and (4) a deceleration phase occurring in most but not all models where extensional velocities decrease. We find that the speed‐up during rifting is compensated by subduction acceleration or subduction initiation even in distant localities. Our study illustrates new links between local rift dynamics, plate motions, and subduction kinematics during times of continental separation.